Artocarpin Targets Focal Adhesion Kinase-Dependent Epithelial to Mesenchymal Transition and Suppresses Migratory-Associated Integrins in Lung Cancer Cells - Nongyao Nonpanya; Kittipong Sanookpan; Nicharat Sriratanasak; Chanida Vinayanuwattikun; Duangdao Wichadakul; Boonchoo Sritularak; Pithi Chanvorachote (MDPI AG, 2021)
Focal adhesion kinase (FAK) controls several cancer aggressive potentials of cell movement and dissemination. As epithelial-mesenchymal transition (EMT) and the migratory-associated integrins, known influencers of metastasis, have been found to be linked with FAK activity, this study unraveled the potential pharmacological effect of artocarpin in targeting FAK resulting in the suppression of EMT and migratory behaviors of lung cancer cells. Treatment with artocarpin was applied at concentrations of 0-10 μM, and the results showed non-cytotoxicity in lung cancer cell lines (A549 and H460), normal lung (BEAS-2B) cells and primary metastatic lung cancer cells (ELC12, ELC16, and ELC20). We also found that artocarpin (0-10 µM) had no effect on cell viability, proliferation, and migration in BEAS-2B cells. For metastasis-related approaches, artocarpin significantly inhibited cell migration, invasion, and filopodia formation. Artocarpin also dramatically suppressed anchorage-independent growth, cancer stem cell (CSC) spheroid formation, and viability of CSC-rich spheroids. For molecular targets of artocarpin action, computational molecular docking revealed that artocarpin had the best binding affinity of −8.0 kcal/mol with FAK protein. Consistently, FAK-downstream proteins, namely active Akt (phosphorylated Akt), active mTOR (phosphorylated mTOR), and Cdc42, and EMT marker and transcription factor (N-cadherin, Vimentin, and Slug), were found to be significantly depleted in response to artocarpin treatment. Furthermore, we found the decrease of Caveolin-1 (Cav-1) accompanied by the reduction of integrin-αν and integrin-β3. Taken together, these findings support the anti-metastasis potentials of the compound to be further developed for cancer therapy.